Antibacterial activity of Coccinia grandis leaf extract on selective bacterial strains - A. Sivaraj, B. Preethi Jenifa, M. Kavitha, P. Inbasekar, B. Senthilkumar, A. Panneerselvam (Journal of Applied Pharmaceutical Science)
AbstractTo assess the antibacterial activities of Coccinia grandis leaf extract on selective bacterial strains under in-vitro conditions. The antibacterial activity was tested against five bacterial strains by agar well diffusion method. The crude extract showed a broad spectrum of antibacterial activity by inhibiting both the gram positive and gram negative groups. The antibacterial activity of C.grandis leaf extract using solvents such as acetone, ethanol, methanol, aqueous and hexane was evaluated against five bacterial sp. Ethanol leaf extract of C.grandis showed high antibacterial activity against S.aureus, B.cereus, E.coli, K.pneumoniae and S.pyogens. Minimal inhibitory concentration of the leaf extract against each test organism was also studied by observing their growth on Mueller Hinton Agar containing the extract at various incremental levels, equivalent to 31.25µg/ml to 1000µg/ml of the extract. The highest activity was observed in ethanol extracts against S.aureus, E.coli, and K.pneumoniae with an inhibitory concentration below 31.5µg/ml. The significance of the study was conducted to investigate the invitro antibacterial activity of folklore medicinal plant and to evaluate scientific base of their applications.
Keywords: Antibacterial, Coccinia grandis, Agar well diffusion, Minimal inhibitory concentration (MIC).